A MASS MIGRATION OF BUTTERFLIES - BONET, FEDERICO (Petróleos Mexicanos, CD MEXICO, DF, MEX, 1943)
Expts were performed indicating that O amblus and O furcosus cannot transmit S turicatae or S venezuelensis by biting; nor can S v be transmitted by O parkeri or O hermsi Inoculations carried out with triturated ticks show that S turicatae and
REV SOC MEX HIST NAT
Keywords: MASS MIGRATION, BUTTERFLIES; CIENCIAS DE LA VIDA; BIOLOGIA ANIMAL (ZOOLOGIA)